Espacios para el más allá: Historia del cementerio de Arica, entre la religiosidad y la secularización (1868-1932) - Pablo Chávez Zúñiga (Nuevo mundo - Mundos Nuevos, 2015)
This work presents an analysis of the mortuary spaces, social practices and the construction of representations linked to the death between 1868 and 1932. The initial part of the research is a contextualization of the spaces of death in Arica (end northern Chile), the earthquake that caused the destruction of the church in the Matrix, the spatial definition of the peripheral cemetery and changes that manifested after the start of the Chilean government. Generated tensions and conflicts between the church and state level around the colonial church cemetery in the Matriz are presented. Finally, the representations and testimonies of subjects are addressed through the wakes and funeral ceremonies.